Iowa Birdline update, November 19, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Email of the Iowa Birdline update for November 19, 1990. Highlights of the update include mostly sightings from northeast Iowa, but two Scoter species were reported in the southwest part of the state. Sightings of note were 500 Tundra Swans, 30 Bald Eagles, Ruffed Grouse, and a pure white albino Red-tailed Hawk. Also included are handwritten notes with sightings of a Snowy Owl, a first year Black-legged Kittiwake, an all-white first winter Glaucous Gull and a Eurasian Tree Sparrow. Epson - sheet feed/flatbed